Corporate Income Tax: Effectiveness in the Context of Public Fiscal Policy and Entrepreneurship Support - Vasilyeva, Tetyana Anatoliivna; Vysochyna, Alina; Taranchenko, Alina (International Journal of Economics, Business, and Entrepreneurship, 2018)
The article analyzes the approaches to the definition of the essence and quantitative assessment of the fiscal effectiveness of the income tax. According to the results of the study, it was found out that the fiscal effectiveness of the income tax can be estimated through the indicators of fiscal importance of the tax in the tax revenues of the state (consolidated) budget; tax burden of the tax (in relation to GDP); elasticity of income tax; effective tax rate and tax productivity, etc. The analysis of the dynamics of these indicators over the past few years in Ukraine has allowed us to confirm the low level of fiscal effectiveness and regulatory potential of this tax for Ukraine. One of the possible ways to improve the fiscal effectiveness of the income tax is to use indirect channels of influence, which are represented by the general state of the country's economic development, labor market efficiency, level of welfare of the population, investment attractiveness, and performance of enterprises. The empirical study of determining the most significant channels of influence on the indicators of fiscal effectiveness of the income tax has made it possible to find out: 1) growth of absolute amounts of income tax revenue can be achieved through the use of the investment channel, budget channel and labor market channel; 2) increase in the tax burden on income tax is contributed by the increase in the revenues of the Consolidated Budget, index of industrial producer prices and consumer price index, and increase of the employment rate, while the improvement of the indicators of the overall economic development of the state and investment climate leads to reduction of the tax burden; 3) increase in the fiscal significance of the income tax is contributed by the increase in growth rate of direct investment, level of employment and real wages. Thus, the analysis conducted allowed to identify the channels through which authorities can influence the fiscal effectiveness of the income tax.